Need to suspect fungal etiology in presumed bacterial keratitis - A case report of keratitis due to Scedosporium prolificans - Chandel, Lata R; Sood, Anuradha; Chauhan, Smriti; Thakur, Kamlesh (Asian Journal of Medical Sciences, 2011)
We describe a case of keratitis with acute presentation and without any history of trauma caused by Scedosporium prolificans; a rare cause of fungal keratitis, from a tertiary care hospital. To the best of our knowledge this is the first such case reported from the region. Because of early diagnosis and prompt treatment the patient could be managed well. Keywords: Keratitis; Scedosporium prolificans; Prompt treatment DOI: 10.3126/ajms.v2i1.4058 Asian Journal of Medical Sciences 2 (2011) 28-30